How keeping up diversifies: Watching public affairs TV in the Netherlands 1988–2010. (December 2013) - Wonneberger, Anke; Schoenbach, Klaus; van Meurs, Lex
Although concerns have been raised that political infotainment programmes might increasingly substitute more serious information, empirical evidence about changes of individual viewing behaviour is scarce. The authors discuss audience specialization and diversification as two opposing patterns of audience response to a growing variety of public affairs programmes. While specialization results from selective programme choice, diversification may be furthered by the impact of situational factors. Using electronically recorded people-meter data, this study explores information viewing in the Netherlands over the last two decades. As opposed to concerns about audience fragmentation, the authors find that public affairs viewing has become more diverse on the individual level with entertaining information programmes used as an additional source of information. Dutch viewers were exposed to different public affairs information. The personal relevance of TV as a medium is one of the main drivers behind high levels of exposure.